A short discourse on vascular tissue engineering - William G. Chang (Nature Portfolio, 2017)
Abstract Vascular tissue engineering has significant potential to make a major impact on a wide array of clinical problems. Continued progress in understanding basic vascular biology will be invaluable in making further advancements. Past and current achievements in tissue engineering of microvasculature to perfuse organ specific constructs, small vessels for dialysis grafts, and modified synthetic and pediatric large caliber-vessel grafts will be discussed. An emphasis will be placed on clinical trial results with small and large-caliber vessel grafts. Challenges to achieving engineered constructs that satisfy the physiologic, immunologic, and manufacturing demands of engineered vasculature will be explored.